Unveiling the Survival Gap: Addressing the Challenges of Acute Lymphoblastic Leukemia in Adolescents - Aisyi, Mururul; Kosasih, Agus Susanto; Utomo, Ahmad Rusdan Handoyo; Saputra, Fahreza; Sari, Teny Tjitra; Sjakti, Hikari Ambara; Dwijayanti, Fifi; Harimurti, Kuntjoro; Andriastuti, Murti (Indonesian Journal of Cancer, 2025)
Background: Acute Lymphoblastic Leukemia (ALL) remains the most common pediatric cancer, yet survival outcomes vary widely across age groups. In Indonesia, comprehensive data on ALL survival rates are sparse, particularly for adolescents who often fare worse than younger children. The underlying factors contributing to the difference in adolescent survival rates still need to be fully understood. This study aimed to evaluate and compare the survival rates of children and adolescents with ALL treated at Dharmais Cancer Hospital.Method: We conducted a retrospective cohort analysis of 94 ALL patients, including 37 adolescent patients and 71 patients with B-lineage ALL. All patients with ALL from 2021 to 2023 were identified. Children aged 1–18 years, diagnosed with ALL based on bone marrow results and not yet treated, are included in the study. Patients were stratified by risk stratification (Standard Risk [SR] vs. High Risk [HR]), lineage (B-lineage vs. T-lineage), and age group (children under 10 vs. adolescents 10 years and above). The survival curve was analyzed using the KaplanMeier method, and the log-rank test was used to assess and compare survival across groups.Results: The overall survival (OS) rate for ALL patients was 49.5%. Adolescents had a significantly lower OS rate of 23.2% compared to children. SR patients exhibited an OS rate of 95.7%, while HR patients had a 33.3%. B-cell lineage had a higher OS rate (59.8%) than T-cell lineage (15.9%). In B-cell ALL, OS was 61.4% in children but only 28.1% in adolescents. Conclusion: The survival rate for adolescents with acute lymphoblastic leukemia (ALL) is significantly lower than that of children, influenced by risk stratification, lineage, and age. Further research is needed to identify these risk factors through genetic and molecular analyses.Conclusion: The survival rate for adolescents with acute lymphoblastic leukemia (ALL) is significantly lower than that of children, influenced by risk stratification, cell type, and age. Unexplained factors, including lineage differences, remain a challenge in adolescents. Further research into genetic and molecular factors is essential to enhance treatment precision and improve survival rates for ALL patients in Indonesia, especially adolescents.Keywords: Overall Survival, Leukemia, Adolescent ALL, Stratification